Hubungan Pengetahuan terhadap Pengontrolan Kadar Kolesterol - Sulayfiyah, Tri Nili; Ida Wahyuni; Atiqur Rohman (Indonesian Health Science Journal, 2024)
Introduction: Cholesterol is a complex fat compound found in the bloodstream or body cells. It plays an important role in the formation of cell walls and is a basic ingredient for several hormones. Knowledge greatly influences behavior in controlling cholesterol, as well as influencing awareness of the importance of controlling cholesterol to prevent an increase in cholesterol. Objective: to analyze the relationship between knowledge and cholesterol control. Method: The design used in this study was a quantitative study using a cross-sectional approach, with a sample of 30 respondents selected through a purposive sampling method. Statistical tests using the Chi-Square Correlation Test with a significance level of 5% (α = 0.05). Results: The results of the Chi-Square test with a significance level of α <0.05 showed a significant value (ρ) of 0.025, which means that the correlation between knowledge and cholesterol control is significant. Conclusion: There is a relationship between knowledge and cholesterol control.